Pelatihan Remaja SMA Imelda Medan dalam Menjaga Kebersihan dan Kesehatan Organ Reproduksi - Purba, Lamtiur; Harahap, Ali Asman; Gultom, Satriani H; Damanik, Candra Meriani (CV. Devi Tara Innovations, 2026)
Adolescent reproductive health is a crucial aspect of public health development, particularly in high school settings. Many students lack accurate knowledge and sufficient skills to maintain the cleanliness and health of their reproductive organs. This community service research aims to improve the knowledge and skills of students at SMA Imelda Medan through educational and demonstrative training. The methods employed included interactive counseling, practical demonstrations on reproductive organ hygiene, and group discussions. Evaluations were conducted using pre-tests and post-tests, accompanied by practical skill observations. The results indicated a significant increase in both knowledge scores and practical skills among students after the training, reflecting the effectiveness of this educational approach. This program is expected to equip students with practical understanding and skills that support healthy behaviors and responsible reproductive health practices.